Assignment of parentage in triploid species using microsatellite markers with null alleles, an example from Pacific oysters (Crassostrea gigas) - Miller, PA; Elliott, NG; Rene Vaillancourt; Anthony Koutoulis; Henshall, JM (2016)
Triploid production in aquaculture is increasing because of their more profitable growth and reproduction traits. Triploids are mostly produced through mass spawning techniques, meaning that exact pedigree is unknown. The ability to trace the pedigree of high performing triploids would allow selection of broodstock to perpetuate triploids of greater economic value. This study aimed to develop a method of determining parental assignment in triploids and test its accuracy on triploid oysters. Using a likelihood approach and accounting for null allele frequencies, a method was developed which proved to be efficient at determining the pedigree of triploid oysters. This method was able to provide accurate pedigree on simulated data and two commercial cohorts of triploid oysters. The analysis of the triploid cohorts showed that mass spawning to produce triploid oysters, like that for diploid and tetraploids, results in a strong bias in parental contributions, with the effective population size being 34-49% lower than the census population. This highlights the need for pedigree control in breeding programs and indicates that the ability to determine parentage of triploids will be a valuable tool for breeding programs.